SARS-CoV-2 infections among asymptomatic individuals contributed to COVID-19 cases: A cross-sectional study among prospective air travelers from Ghana - Akowuah, Kwasi A.; Akuffo, Richard A.; Boateng, Anthony T.; Asigbee, Theodore W.; Bonney, Joseph H. K.; Lamptey, Helena; Adusei-Poku, Mildred A.; Obodai, Evangeline; Asante, Ivy A.; Adjei, Samuel; Aboagye, James O.; Adu-Amankwah, Susan; et al. (Frontiers in Public Health, 2022)
Background The spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by asymptomatic individuals has been reported since the early stages of the coronavirus disease 2019 (COVID-19) outbreak in various parts of the world. However, there are limited data regarding SARS-CoV-2 among asymptomatic individuals in Ghana. The aim of the study was to use test data of prospective travelers from Ghana as a proxy to estimate the contribution of asymptomatic cases to the spread of COVID-19. Methods The study analyzed the SARS-CoV-2 PCR test data of clients whose purpose for testing was classified as “Travel” at the COVID-19 walk-in test center of the Noguchi Memorial Institute for Medical Research (NMIMR) from July 2020 to July 2021. These individuals requesting tests for travel generally had no clinical symptoms of COVID-19 at the time of testing. Data were processed and analyzed using Microsoft Excel office 16 and STATA version 16. Descriptive statistics were used to summarize data on test and demographic characteristics. Results Out of 42,997 samples tested at the center within that period, 28,384 (66.0%) were classified as “Travel” tests. Of these, 1,900 (6.7%) tested positive for SARS-CoV-2. The majority (64.8%) of the “Travel” tests were requested by men. The men recorded a SARS-CoV-2 positivity of 6.9% compared to the 6.4% observed among women. Test requests for SARS-CoV-2 were received from all regions of Ghana, with a majority (83.3%) received from the Greater Accra Region. Although the Eastern region recorded the highest SARS-CoV-2 positivity rate of 8.35%, the Greater Accra region contributed 81% to the total number of SARS-CoV-2 positive cases detected within the period of study. Conclusion Our study found substantial SARS-CoV-2 positivity among asymptomatic individuals who, without the requirement for a negative SARS-CoV-2 result for travel, would have no reason to test. These asymptomatic SARS-CoV-2-infected individuals could have traveled to other countries and unintentionally spread the virus. Our findings call for enhanced tracing and testing of asymptomatic contacts of individuals who tested positive for SARS-CoV-2.